Resistance training for distance running: A brief update - Jones, P.; Bampouras, T. M. (Strength and Conditioning Journal, 2007)
The positive effects of resistance training on distance-running performance through enhanced running economy are well established. However, few practical recommendations exist to aid coaches in planning resistance training to supplement a distance-running program. This article reviews literature in this area and offers practical applications for the athletics coach.